Анализ проблем восприятия абитуриентами специальности "Маркетинг" (на примере Сумской области) - Ильяшенко, Сергей Николаевич; Карпищенко, Марина Юрьевна (Сумський державний університет, 2011)
Изложены результаты исследования потребительских предпочтений на рынке образовательных услуг Сумской области, а также проблем восприятия потенциальными абитуриентами специальности "Маркетинг". Определены факторы, влияющие на выбор профессии маркетолога.

It is presented the results of studies of consumer preferences in the educational market of Sumy region, as well as problems of potential applicants’ perception of the specialty "Marketing". It is defined factors which influence to the choice the profession of a marketer.
Analysis of problems of entrants’ perception the speciality "Marketing" (on the example of Sumy region)
Keywords: рынок образовательных услуг; высшее образование; маркетинговые исследования; потребительские предпочтения; факторы влияния; коммерческие предприятия; market of educational services; higher education; market research; consumer preferences; factors of influence